Deep Reinforcement Learning and Generative Adversarial Networks for Portfolio Optimization: An Innovative Approach to Enhance Investment Strategies - Zarinabegam Mundargi (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This research project presents an innovative approach to portfolio optimization by integrating Deep Reinforcement Learning (DRL) and Generative Adversarial Networks (QUANTUM GANs). The objective is to develop an intelligent portfolio management system that learns optimal investment strategies through DRL and generates synthetic portfolios aligned with predefined objectives using QUANTUM GANs. The synergy between these two machine learning paradigms aims to address the challenges posed by traditional portfolio optimization methods, offering a dynamic and adaptive solution in response to evolving market conditions. The DRL component of the system employs advanced algorithms to enable an intelligent agent to make real-time investment decisions based on historical financial data. This autonomous learning process allows the portfolio to adapt and optimize strategies, balancing risk and return dynamically. By generating synthetic portfolios, the system enhances diversification possibilities and adapts to various market scenarios. This unique combination of DRL and QUANTUM GANs opens new avenues for strategic decision-making, risk mitigation, and exploration of portfolio possibilities.